2016
DOI: 10.1021/acschembio.6b00324
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Selectively Alters the Intracellular Localization of Desmosterol

Abstract: Hepatitis C virus (HCV) increases intracellular desmosterol without affecting the steady-state abundance of other sterols, and the antiviral activity of inhibitors of desmosterol synthesis is suppressed by the addition of exogenous desmosterol. These observations suggest a model in which desmosterol has a specific function, direct or indirect, in HCV replication and that HCV alters desmosterol homeostasis to promote viral replication. Here, we use stimulated Raman scattering (SRS) microscopy in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…With SRS imaging, they were able to reveal heterogeneous partitioning of free cholesterol, cholesterol ester and triglyceride into LDs (Figure 3C and D). In another study 37 , d 6 -desmosterol was found accumulated in LDs when the cells were infected by hepatitis C virus.…”
Section: Lipid Metabolismmentioning
confidence: 87%
“…With SRS imaging, they were able to reveal heterogeneous partitioning of free cholesterol, cholesterol ester and triglyceride into LDs (Figure 3C and D). In another study 37 , d 6 -desmosterol was found accumulated in LDs when the cells were infected by hepatitis C virus.…”
Section: Lipid Metabolismmentioning
confidence: 87%
“…Desmosterol has been detected in replicase-containing membranes by LC-MS analysis ( Figure 2) and in NS5Aassociated lipid droplets by stimulated Raman scattering microscopy 11 . 11 . Pharmacological inhibition of DHCR7 leads to depletion of intracellular desmosterol and a profound reduction in both HCV proteins and genomic RNA that is rescued by the addition of exogenous desmosterol.…”
Section: Figure 1 the Membranous Web Is A Specialized Membranous Enmentioning
confidence: 99%
“…For example, many RNA viruses, including HCV, are known to remodel sections of the host ER membrane to form specialized replication compartments ( 37 41 ). In our previous work, we have documented specific HCV-induced changes to host lipid metabolism, including a large-fold increase in desmosterol ( 15 , 16 ). Enrichment of desmosterol in the membrane where viral RNA replication occurs is, moreover, correlated with an increase in the diffusivity of the membranes where RNA replication occurs ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Huh7.5–SGR cells stably replicating the HCV JFH1 (2a) subgenomic replicon were generated by electroporation of Huh7.5 cells with in vitro transcribed replicon RNA as previously described ( 18 ). Huh7.5–SGR cells were maintained in Dulbecco's modified Eagle's medium supplemented with nonessential amino acids, 10% fetal bovine serum (Invitrogen), and G418 sulfate (750 µg/ml final concentration) ( 15 , 16 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation